Melestarikan dan Mengembangkan Warisan Budaya: Kebijakan Budaya Semarangan Dalam Perspektif Sejarah - Dhanang Respati Puguh (Jurnal Sejarah Citra Lekha, 2017)
Semarang has developed as a diverse city. The communities who lived in Semarang history has produced a hybrid culture patterned Semarang which in the next time become as "Semarangan culture". At that time of Indonesia's independence there is awareness to preserve the cultural heritage of Semarangan either by local governments and communities of Semarang. The preservation and development cultural heritage of Semarangan continues which among other things aims to establish a cultural identity for the community and theie city. However, such efforts have not been able to achieve the expected results, because the Semarangan culture is less able to perform in a stage of cultural life in their own city and national culture.